The Chaos in Translating Critical Terminology between Eastern and Western Arab Scholars: Intertextuality Terminology as a Case Study - midaouar, medemed (El Omda in Linguistics and Discourse Analysis, 2023)
This research attempts to discover the chaos that characterizes the translation of literary criticism terms from a foreign language into Arabic, through a comparison between Moroccan translators and the Orientals ; Taking the terminology of intertextuality theory as a model for study because it is one of the most common terms in Arabic critical discourse. We will focus our attention on two translations of two books, namely: "Introduction to Intertextuality" which was translated by the Algerian researcher, "Abdel-Hamid Borayo", and the second is the book "The Theory of Intertextuality", which was translated by the Syrian “Basil Al-Masalmah